CAMELLIA SINENSIS (L.) O. KUNTZE AND ITS BENEFICIAL SOIL MICROFLORA - Renla, Temsu; Ajungla, T (Innovare Journal of Life Sciences, 2017)
Since time immemorial, humans have been using leaves of tea plant (Camellia sinensis L.) O. Kuntze as medicinal beverage. Till date, one cannot determine the extent to which it can benefit us both medicinally as well as economically. Therefore, looking at the popularity of tea in global market, studying and collecting information on chemical compounds of tea leaves becomes important to develop well informed strategies for expanding and enhancing the utilization of these chemicals in beverage and food industry. In order for tea plant to produce quality products, it need to be healthy and this can be achieved only when the place where it grows provide necessary elements required by the plant at the right time. So, in addition to factors like season, climate and physiochemical properties of soil, it is necessary to give importance to soil microbes as well for they are an important part of biogeochemical cycles of the earth and also possess many abilities like degradation of synthetic chemicals, promoting plant growth, solubilise nutrients, fixes nitrogen, enzyme degradation, control of pests and diseases. Keywords: Camellia sinensis, Physiochemical, Microbes, Biogeochemical.